A Comprehensive Review of Ultrahigh Molecular Weight Polyethylene Fibers for Applications Based on Their Different Preparation Techniques - Omar Faruk; Yang Yang; Jiangliang Zhang; Junxin Yu; Jiaojiao Lv; Weichao Lv; Yueying Du; Jindan Wu; Dongming Qi (Advances in Polymer Technology)
Ultrahigh molecular weight polyethylene (UHMWPE) fiber is widely recognized for its exceptional properties, including high strength-to-weight ratio, toughness, and chemical resistance, making it a preferred material for reinforcement in various applications. However, its low melting point, surface inertness, and weak adhesion to polymer matrices have limited its potential use in some fields. Researchers have addressed these shortcomings by focusing on surface modifications through physical treatment or chemical coating, thereby enhancing the versatility of materials in numerous UHMWPE fiber composites. By improving the tribological and interfacial properties of UHMWPE, various applications can be explored, including prosthetic joints, energy-absorbing road safety systems, microelectromechanical system devices, and protective materials for defense and personal thermal management. This review provides a comprehensive overview of the remarkable performance of UHMWPE and its composites, providing insights into its wide array of applications.